(untitled) (CIPEEX, 2025)
The objective of this research project is to compare the effects of a psychomotor intervention program based on the organization of therapeutic settings in cycles, with the effects obtained by a conventional psychomotor intervention program based on a circuit of activities on the motor development and participation of children with Autism Spectrum Disorder (ASD). This is a randomized, blinded, controlled clinical trial involving 30 children diagnosed with ASD. Participants will be assessed one week before the intervention, one week and one month after the end of the interventions, using the Childhood Autism Rating Scale, Autism Classification System: Social Communication, Motor Development Assessment Battery, and Participation and Environment Measure - Children and Youth. The interventions will consist of two sessions per week, carried out over four consecutive weeks, totaling eight sessions lasting 45 minutes each. The experimental group will undergo the psychomotor intervention program based on the organization of Therapeutic Settings in cycles. The control group will undergo the psychomotor intervention program. In both interventions, the psychomotor structures of balance, tone, body awareness, laterality, spatial organization, gross motor skills, and fine motor skills will be focused on in the proposed activities. The results will be analyzed statistically assuming a significance level of p≤0.05.